The impact of public participatory environmental regulation on carbon emission intensity: a policy text analysis - Wu, Jianzu; Yu, Zhipiao; Wang, Rongjuan (Frontiers in Environmental Science, 2025)
Carbon emissions have emerged as a critical global environmental challenge, with public participatory environmental regulation becoming an increasingly vital governance tool in promoting carbon reduction. This study employs panel data from 278 prefecture-level cities in China spanning 2011–2020 to construct a public participatory environmental regulation index through policy text analysis, empirically examining its impact mechanism on carbon emission intensity. The findings reveal that: (1) public participatory environmental regulation significantly reduces carbon emission intensity; specifically, baseline regression results indicate that a one-unit increase in public participatory environmental regulation intensity leads to a 0.05 unit decrease in carbon emission intensity, significant at the 1% level; (2) mediation analysis demonstrates that public environmental participation serves as a significant intermediary between environmental regulation and carbon emission reduction; (3) heterogeneity analysis indicates that official characteristics significantly moderate policy effectiveness, with regulations implemented by non-local, shorter-tenured, and less-educated officials showing stronger inhibitory effects on carbon emissions compared to their counterparts. These findings underscore the importance of strengthening public participation mechanisms in environmental governance and considering official characteristics in policy implementation. This study provides both theoretical foundations for optimizing public participatory environmental regulation policies and practical implications for enhancing carbon reduction effectiveness.